Learning to Live with Dungalaba: Embracing Indigenous Knowledge Practises for Respectful Coexistence with Saltwater Crocodiles in the Northern Territory - Lachlan Saunders; Scott Jukes (Australian Journal of Environmental Education)
In this paper, we focus on a particular example of human–wildlife conflict involving Dungalaba (Dungalaba, Saltwater Crocodile, C. porosus — this paper will interchange between the various names of the species. It is preferred to us various names as we would like to acknowledge the various ways in which people come to understand and recognise the species) (Saltwater Crocodile) in the Northern Territory, Australia. We seek to both better understand and improve relationships with such potentially dangerous animals, positioning this as an educational endeavour. Drawing upon interviews with a small number of relevant stakeholders, we utilise storytelling as a method for informing contemporary relationships with Dungalaba. The method of storytelling has been used effectively by Indigenous Australians for thousands of years to pass teachings of our older people for the benefit of future generations. During interviews, research participants told stories of their lived experiences, which informed the creation of narratives that depict current relationships of conflict and past relationships of harmony. We discuss these narratives and how they may educate for respectful interactions and mutually beneficial coexistence between humans and Dungalaba. This paper contributes to the growing body of work that embraces Indigenous ways of knowing for improved environmental relations. Furthermore, this paper offers specific possibilities for the use storytelling as a tool within crocodile safety education programs within the Northern Territory.